Desain Produk dan Jasa Manajemen Operasional - Hikhmah Dzil Hijjah; Adi Mansah (An Nafi': Multidisciplinary Science, 2024)
The article "Desain Produk dan Jasa Manajemen Operasional" discusses the importance of operational management in producing quality products and services efficiently and effectively. In today's globalized era, businesses face intense competition and must produce high-quality products and services at minimal costs. Therefore, product and service design is crucial in operational management. Good product and service design can increase a company's competitiveness, provide greater profits, and enhance customer satisfaction and corporate image. In designing products and services, companies must consider various aspects such as function, aesthetics, ergonomics, and safety.Operational management also involves managing the production and service processes, supply chain, and technology. Companies must manage the production and service processes efficiently produces high quality products and services. minimal costs. They must also manage the supply chain effectively to obtain quality raw materials and components at affordable prices. Technology plays a vital role in operational management, and companies must leverage it to increase efficiency and effectiveness in production and service processes.The literature review covers the definitions and explanations of design products, services, operational management, management, and service operational management. The discussion focuses on the impact of product design on operational efficiency, and the operational management strategies that support product design. Finally, the article emphasizes its importance. product and service design in operational management. It also emphasizes the need for efficient production and service processes, effective supply chain management and the use of technology to increase efficiency and. effectiveness. The article provides insights into the various aspects of operational management and how they relate to product and service design. The information in this article may help. businesses improve their operational management practices and produce high-quality products and services at minimal costs.